Flood, disaster resilience and social cohesion informing sustainable disaster recovery policy in Malaysia - Mohamed Ludin, Salizar; Firdaus, Mohd Khairul Zul Hasymi; Yusoff, D; Arbon, Paul (2016)
Introduction: In responding to the post-2015 “Sendai framework for disaster risk reduction” (UNISDR 2015), countries across the globe have emphasized the important role of local government and community organization support in implementing community resilience programs. However, despite the Malaysian Government acknowledging the need to review and redevelop Malaysia’s sustainable disaster recovery policies and post-disaster rebuilding programs, the level of Malaysia’s community disaster resilience and cohesiveness and how to measure it are unknown.